Safety assessment of the substance poly((R)‐3‐hydroxybutyrate‐co‐(R)‐3‐hydroxyhexanoate) for use in food contact materials. (20th July 2018) - ,; Silano, Vittorio; Bolognesi, Claudia; Chipman, Kevin; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; Kärenlampi, Sirpa; et al.
Abstract: This opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety assessment of poly(( R )‐3‐hydroxybutyrate‐co‐( R )‐3‐hydroxyhexanoate), Chemical Abstracts Service (CAS) No 147398‐31‐0 and food contact material (FCM) substance No 1059, for contact with dry/solid food. This biodegradable (co)polymer is produced by fermentation of palm oil using a genetically modified microorganism ( Cupriavidus necator ). No migration of oligomers into food simulant E (10 days at 40 and 60°C) was found at a detection limit per single oligomer of 5 μg/kg food. Migration of the degradation product crotonic acid was 8 and 25 μg/kg at the two test temperatures, respectively. The other migrating substances detected, ■■■■■, likely originated from or are related to the authorised substance (FCM No. 9) 'palm oil and/or palm fatty acid distillate' used as carbon source for the fermentation. At the migration levels reported, these migrants do not give rise to safety concern. No genotoxicity data are required for poly(( R )‐3‐hydroxybutyrate‐co‐( R )‐3‐hydroxyhexanoate) because of its high molecular weight. The fraction below 1, 000 Da is 0.5%. The major monomeric unit in the copolymer, 3‐hydroxybutyric acid, is an intermediate in fatty acid metabolism. The minor monomeric unit, 3‐hydroxyhexanoic acid, tested negative for bacterial gene mutations. Degradation products, which may be present in the (co)polymer, are crotonic acid and ( E )‐2‐hexenoic acid. Crotonic acid is authorised for use in FCM with a specific migration limit (SML) of 0.05 mg/kg food; for ( E )‐2‐hexenoic acid, no indication for genotoxicity was identified by the EFSA CEF Panel in its 2010 group evaluation of flavouring substances in FGE.05Rev2. The CEF Panel concluded that the substance poly(( R )‐3‐hydroxybutyrate‐co‐( R )‐3‐hydroxyhexanoate) is not of safety concern if used alone or in blends with other polymers for contact with dry/solid food. If the SML of crotonic acid is met, migration of ( E )‐2‐hexenoic acid will also not exceed 0.05 mg/kg food.